Elasticity and fracture strain of whole blood clots - Riha, P; Wang, X; Liao, R; Stoltz, J F (Clinical hemorheology and microcirculation, 1999)
The measurement of clot elasticity and fracture strain is carried out using a rotational rheometer with a controlled stress system. The elasticity is quantified by a shear elastic modulus and fracture strain by a critical strain (deformation) when the clot begins to break up. The results indicate a decrease of elasticity and increase of fracture strain of the clot with increasing hematocrit. Moreover, the elastic modulus of the clot is not constant but increasing with deformation.
Keywords: Blood Platelets; trombocyty; erytrocyty; Blood Coagulation; Humans; Elasticity; Hematocrit; pružnost; lidé; hematokrit; Erythrocytes; hemokoagulace; počet erytrocytů; Erythrocyte Count